The Tragedy of the Nurdles: Governing Global Externalities - Murtazashvili, Ilia; Rayamajhee, Veeshan; Taylor, Keith (Sustainability, 2023)
Nurdles have been referred to by some as a global environmental disaster. However, relative to the controversies surrounding industrial fracking practices, such as public health and safety associated with extraction of shale gas (as well as shale oil), the problems with nurdles are not as widely known. In this article, we highlight that fracking and nurdles are interrelated: fracking processes are a major source of the raw materials used to produce nurdles, which are tiny plastic pellets polluting our waters. Our contention is that a key question for analysis of fracking is how to regulate the externalities associated with downstream products produced in the fracking process. This article takes insights from Elinor Ostrom and scholars of the Bloomington School of Political Economy—such as polycentricity, diversity of collective action problems (CAPs), coproduction, and institutional diversity—to analyze nurdles pollution as a global commons problem. Nurdles generate widespread, large-scale negative externalities that are difficult to contain and address within a fixed geographical boundary governed by a static jurisdictional authority. Using the case of the Royal Dutch Shell cracker plant in Beaver County, Pennsylvania, we show that nurdles present complex and nested challenges that require coproduction, with citizen monitoring playing an essential role in mitigating negative externalities. We demonstrate the efficacy of applying polycentric approaches toward addressing CAPs associated with nurdles.